Phylogenetic Analysis Cantigi Ungu (Vaccinium Varingifolium (Blume) Miq.) Plant Growing in the Highlands of West Java Based on Internal Transcribed Spacer (ITS) Gene - Muhammad Haidar Amrullah; Andi Salamah (CV. Publikasi Indonesia, 2026)
Cantigi Ungu (Vaccinium varingifolium (Blume) Miq.) is an endemic plant of Java that is found in mountainous areas at altitudes ranging from 1,800 to 2,000 m above sea level. It is known by several local names, including Cantigi Ungu, Mentigi, Manis Rejo, and Delima Manda. To date, genetic data reports on this plant remain limited. Genetic conservation efforts are necessary to ensure the sustainability, availability, and preservation of this plant’s germplasm, as well as to determine its conservation status. This study aims to analyze the phylogenetic relationships of Cantigi Ungu plants growing in the highlands of West Java based on Internal Transcribed Spacer (ITS) gene sequences. The research was conducted on three Cantigi Ungu plants collected from the highlands of West Java, specifically within the Mount Gede Pangrango National Park area, Mount Tangkuban Parahu Nature Park, and Kawah Putih, and their ITS gene sequences were compared. ITS gene amplification was performed using the forward primer ITS_u1 (5′-GGA AGK ARA AGT CGT AAC AAG G-3′) and the reverse primer ITS_u4 (5′-RGT TTC TTT TCC TCT GCT TA-3′). Phylogenetic analysis was conducted using MEGA XI software with the Maximum Likelihood (ML), Minimum Evolution (ME), Neighbor-Joining (NJ), and Maximum Parsimony (MP) methods. The results showed that the Cantigi Ungu samples analyzed in this study belong to the same species as the reference species, Vaccinium varingifolium, with accession number AY274564.1.